MAdCAM-1-Mediated Intestinal Lymphocyte Homing Is Critical for the Development of Active Experimental Autoimmune Encephalomyelitis - Kuhbandner, Kristina; Hammer, Anna; Haase, Stefanie; Terbrack, Elisa; Hoffmann, Alana; Schippers, Angela; Wagner, Norbert; Hussain, Rehana Z.; Miller-Little, William A.; Koh, Andrew Y.; Stoolman, Joshua S.; Segal, Benjamin M.; et al. (Frontiers in Immunology, 2019)
Lymphocyte homing into the intestine is mediated by binding of leukocytes to mucosal addressin cell adhesion molecule 1 (MAdCAM-1), expressed on endothelial cells. Currently, the immune system of the gut is considered a major modulator not only of inflammatory bowel disease, but also of extra-intestinal autoimmune disorders, including multiple sclerosis (MS). Despite of intense research in this field, the exact role of the intestine in the pathogenesis of (neuro-)inflammatory disease conditions remains to be clarified. This prompted us to investigate the role of MAdCAM-1 in immunological processes in the intestine during T cell mediated autoimmunity of the central nervous system (CNS). Using the experimental autoimmune encephalomyelitis model of MS, we show that MAdCAM-1 deficient (MAdCAM-1-KO) mice are less susceptible to actively MOG35-55-induced disease. Protection from disease was accompanied by decreased numbers of immune cells in the lamina propria and Peyer’s patches as well as reduced immune cell infiltration into the spinal cord. MOG35-55-recall responses were intact in other secondary lymphoid organs of MAdCAM-1-KO mice. The composition of specific bacterial groups within the microbiome did not differ between MAdCAM-1-KO mice and controls, while MAdCAM-1 deficiency severely impaired migration of MOG35-55 activated lymphocytes to the gut. Our data indicate a critical role of MAdCAM-1 in the development of CNS inflammation by regulating lymphocyte homing to the intestine, and may suggest a role for the intestinal tract in educating lymphocytes to become encephalitogenic.